FENOMENA CHILDFREE DI JEPANG DALAM PERSPEKTIF TEORI FEMINISME EKSISTENSIALIS - Sandra Dewi, Nabila Utami; Ela, Mika; Savira, Aisyah; Triyanti, Febi (Regalia: Jurnal Riset Gender dan Anak, 2022)
Childfree is a decision not to have children voluntarily, this decision can be taken by single men and women but also by married couples. The decision in some countries is still inviting debate among the public but different things have happened in Japan. The Japanese people tend to justify this choice, in fact the Japanese government rejects the child-free decision of its people and even calls the decision something selfish. The Japanese government seeks various programs to increase the birth rate in the country. The issue of childfree in Japan will be studied using existentialist feminism theory which describes women as an object that must be managed by men. The existentialist feminism theory was chosen because it can explain the phenomenon of child-free entering the domestic realm.